Design and Implementation of a Student Biographical Questionnaire (BQ) Online Platform for Effective Student Success (Journal of Student Affairs in Africa, 2021)
Knowing relevant information about students entering the higher education (HE) system is becoming increasingly important, thus enabling higher education institutions (HEIs) to design effective studentcentredsupport programmes. Therefore, HEIs should ascertain all relevant information about their students before the commencement of the academic year. Doing so means that institutions have a head start in understanding the types of support that will be required for different students throughout the year. This article describes the design, implementation and application of a student biographical questionnaire (BQ) online platform at the University of the Witwatersrand (Wits), as well as some of the lessons learned in this regard. The BQ online platform was fully implemented for the first time in January 2016 during the student registration process and has now become an integral part of the university student registration process. Once data collection and analysis is done, a BQ report is compiled and presented to various high-level decision-making structures of the university. The Faculty Student Advisers are the mostcritical users of the BQ data, as they utilise the data to inform and improve the various studentsupport interventions that each faculty is providing. The planning process for BQ data collectionincludes questionnaire review; updates on the BQ online platform; testing of the BQ online platform; stakeholder meetings and BQ training of involved stakeholders. Some of the lessons learned whenimplementing this online platform include buy-in and support from University Management;understanding of the BQ online platform by those dealing directly with students during the registrationprocess; and continuous review and improvements of the BQ online platform. The BQ online platformhas proven to be a valuable tool in providing Wits with a head start in understanding the needs of thestudents and the support they might require to succeed in their first year of study.
Keywords: biographical questionnaire; first-year students; student success; student support; South Africa